2014
DOI: 10.1007/s12598-014-0327-y
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of photocatalytic activity of high specific surface area graphitic carbon nitride by loading a co-catalyst

Abstract: Graphitic carbon nitride (g-C 3 N 4 ) was synthesized by heating melamine and was then treated with sodium hydroxide solution under a hydrothermal condition to obtain g-C 3 N 4 with a large specific surface area (HSSA). HSSA shows higher photocatalytic activity for decomposition of acetaldehyde than that of original g-C 3 N 4 . HSSA was modified with RuO 2 as a co-catalyst by the impregnation method. HSSA loaded with 0.05 wt% RuO 2 shows the highest photocatalytic activity for acetaldehyde decomposition under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 35 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…[3] However, it shows moderate photocatalytic activity due to limited light absorption, low surface area, and rapid recombination of photoexcitons. [4] Therefore, many modification strategies have been employed to improve its photocatalytic performance, such as nanostructure engineering, [5] doping, [6] co-catalyst loading, [7] and heterostructure construction. [8] Formation of heterostructure is regarded as a promising approach to facilitate the separation of photoexcitons, inhibit charge-carrier recombination, and extend the optical absorption.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] However, it shows moderate photocatalytic activity due to limited light absorption, low surface area, and rapid recombination of photoexcitons. [4] Therefore, many modification strategies have been employed to improve its photocatalytic performance, such as nanostructure engineering, [5] doping, [6] co-catalyst loading, [7] and heterostructure construction. [8] Formation of heterostructure is regarded as a promising approach to facilitate the separation of photoexcitons, inhibit charge-carrier recombination, and extend the optical absorption.…”
Section: Introductionmentioning
confidence: 99%
“…However, it shows moderate photocatalytic activity due to limited light absorption, low surface area, and rapid recombination of photoexcitons [4] . Therefore, many modification strategies have been employed to improve its photocatalytic performance, such as nanostructure engineering, [5] doping, [6] co‐catalyst loading, [7] and heterostructure construction [8] …”
Section: Introductionmentioning
confidence: 99%
“…[ 18 ] However, a TiO 2 photocatalyst, [ 19,20 ] which can only absorb UV light (approximately 5% of the total solar radiation), experiences difficulty in utilizing most of the energy in sunlight. [ 21,22 ] To address this problem, various photocatalysts with narrow bandgaps, for example, CdS, [ 23–25 ] g‐C 3 N 4 , [ 26–31 ] BiVO 4 , [ 32–35 ] and ZnIn 2 S 4 , [ 36,37 ] have been gradually developed and utilized. Taking advantage of their strong response to visible light (approximately 40% of the total solar radiation) and appropriate redox potential, these photocatalysts have been widely applied to a variety of photocatalytic systems.…”
Section: Introductionmentioning
confidence: 99%
“…Among the g-C 3 N 4 -based heteronanostructured photocatalysts, RuO 2 nanoparticle (NP)-loaded g-C 3 N 4 (RuO 2 /g-C 3 N 4 ) has recently drawn much interest. For example, Zhang and co-workers have reported that the photocatalytic activity of g-C 3 N 4 with a large specific surface area of 45 m 2 g –1 for acetaldehyde decomposition is significantly improved by loading RuO 2 NPs by the conventional impregnation (Im) method . Chen and Shimoyama and co-workers have recently reported that RuO 2 NP ( d RuO2 = 3.5 nm)-embedded g-C 3 N 4 prepared by an Im method exhibits high photocatalytic activity for H 2 evolution from an aqueous solution of alkanolamines.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Zhang and co-workers have reported that the photocatalytic activity of g-C 3 N 4 with a large specific surface area of 45 m 2 g −1 for acetaldehyde decomposition is significantly improved by loading RuO 2 NPs by the conventional impregnation (Im) method. 8 Chen and Shimoyama and co-workers have recently reported that RuO 2 NP (d RuO2 = 3.5 nm)-embedded g-C 3 N 4 prepared by an Im method exhibits high photocatalytic activity for H 2 evolution from an aqueous solution of alkanolamines. The authors attributed the photocatalytic activity to the catalytic action of the RuO 2 NPs as alkanolamine oxidation rather than H 2 evolution.…”
Section: ■ Introductionmentioning
confidence: 99%